Analysis of Energy Saving Opportunities in Steel Thermal Processing - Kakaš, Damir (Journal of Production Engineering, 1985)
In this paper, an analysis of the issues related to energy conservation in the heat treatment of metals is presented. A review of potential methods for reducing energy consumption in heat treatment is provided, along with an overview of the current situation in the SAP Vojvodina industry. The paper concludes by discussing future developments in this field.